ACQUIRED NEONATAL SEVERE FACTOR II DEFICIENCY- TWO CASES REPORT - Zhu, George (Universal Journal of Pharmaceutical Research, 2022)
In present study two cases of transient acquired and isolated factor II deficiency associated with severe bleeding are reported. Two infants were involved in severe coagulopathy. The blood clot time (CT) in case 2 was excessively prolonged over 16 hours. One-stage prothrombin time (PT) was remarkable prolonged. Haemostatic markers analysis showed an isolated deficiency of factor II at 2.5% and 4.5% respectively. No inhibitory activity against factor II could be detected. We successfully treated the deficiency with vitamin K1 during 15 days. It was interesting that in the case 2 female baby the cause of vitamin K deficiency might be breast feed problem (nutrition deficiency) and/or poor absorption from bowel. Physiopathological laboratory results and therapeutic aspects of two patients were presented. Peer Review History: Received: 1 October 2021; Revised: 11 November; Accepted: 12 December; Available online: 15 January 2022 Academic Editor: Dr. Sally A. El-Zahaby , Pharos University in Alexandria, Egypt, sally.elzahaby@yahoo.com Reviewers: Prof. Dr. Hassan A.H. Al-Shamahy, Sana'a University, Yemen, shmahe@yemen.net.ye Dr. Ogbonna B. Onyebuchi, Nnamdi Azikiwe University, Awka, Nigeria, summitpharm@yahoo.com